1990
DOI: 10.1259/0007-1285-63-753-673
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging, computed tomography and endosonography in the local staging of carcinoma of the cervix

Abstract: Thirty-seven patients with carcinoma of the cervix were prospectively staged by examination under anaesthesia (EUA), transvaginal and transrectal ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI). Pathological correlation was available for 20 patients. In the pathologically staged patients, EUA agreed with the staging in 17, understaging three patients. Endosonography agreed with the staging in 19, CT in 16 and MRI in 18 patients. For the remaining 17 patients, endosonography agreed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Gitsch et al 45 reported the high specificity of diagnosing parametrial invasion based on sonographic features of stromal reaction. Cobby et al 46 reported accuracy rates of 95% for ultrasonography, 85% for clinical examination, and 90% for MRI for local staging or evaluation of parametrial involvement; not all patients in that study underwent surgical staging.…”
Section: Ultrasonographymentioning
confidence: 84%
“…Gitsch et al 45 reported the high specificity of diagnosing parametrial invasion based on sonographic features of stromal reaction. Cobby et al 46 reported accuracy rates of 95% for ultrasonography, 85% for clinical examination, and 90% for MRI for local staging or evaluation of parametrial involvement; not all patients in that study underwent surgical staging.…”
Section: Ultrasonographymentioning
confidence: 84%
“…Successful treatment that improves outcomes in cervical cancer requires accurate evaluation (Fischerova 2011). There has been a great deal of research on pre-operative assessment in patients with cervical cancer (Cobby et al 1990;Zalewski et al 2010), and imaging is complementary to clinical assessment. Despite being used in gynecology for a relatively short period, transvaginal ultrasound shows promise as a method for staging invasive cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1984 when Bies and his coworkers published their experience in comparison of clinical staging with the CT, MR and surgical findings in gynecological tumors magnetic resonance imaging plays a more and more important role in the accurate staging of cervical malignancies (15). With a prospective study it was shown that endosonography and MRI are more accurate than CT in the local staging (16). MRI-based diagnosis enables the determination of a correct tumor staging preoperatively, and is therefore very helpful in planning an adequate therapy.…”
Section: Discussionmentioning
confidence: 99%